Pengaruh Laba Akuntansi dan Aliran Kas Operasional Terhadap Nilai Perusahaan pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Naning Fatmawatie (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2021)
The corporate value that is reflected from share price hanging on operational cash flows future and has positive relation connected with dividend policies, recall that operating cash flows are: (a) measure all from reward; and (b) measure liquidity companies. These cases show that operational cash flows are very important to explain dividend policies, so operational cash flows that good forester from dividend policies to be compared to accounting return. Those become the main subject of this research, that is accounting return, operational cash flows, and corporate value. Populations in this research are all companies listed in Jakarta Islamic Index (JII) during the observation period 2006 to 2008 and 18 companies are selected using non-probability purposive sampling Reference Pasar modal (PRPM-Indonesian Capital Market Reference Center) Indonesia, BAPEPAM, and Pusat Dokumentasi Bisnis Indonesia(Indonesia’s Business Documentation Center), and Indonesian Securities Market Database (ISMD) PPA UNIBRAW. The result shows that accounting return and operational cash flows have influenced positives with corporate value